Fuel Subsidy Removal: Implications on the Living Standards of Low-Income Households in Osun State, Nigeria - Oderinde, Segun; Ogunleye, Akin George; Awotayo, Olagoke Oluwafemi (Department of Social Development and Welfare, Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2025)
This study examines the implications of fuel subsidy removal on the living standards of low-income households in Osun State, Nigeria. A descriptive research design was employed, and a sample of 500 respondents was selected across all thirty local governments in the State. The sample size was determined based on the research questions and the need to achieve a representative sample of low-income households. The study draws on the Sustainable Livelihoods Approach (SLA), which provides a framework for understanding the implications of fuel subsidy removal. The findings reveal that the removal of fuel subsidies has led to increased costs of food, transportation, and other essential goods, resulting in significant hardship for low-income households. The study concludes that, to prevent further poverty and hardship, the Nigerian government should provide targeted support to low-income households, including social protection programmes and support measures to alleviate the economic disruptions caused by fuel subsidy removal and enhance sustainable livelihoods.